Marriage law in household accounting in Indonesia - Hadi, Dudi Abdul; Agustina, Ingrid Larasati; Nuryaman, Nuryaman (Jurnal Mantik, 2024)
This research seeks to reveal what entities are served by household accounting and the practices it commonly implements in society. This research uses the interview method to explore scientific facts related to marriage and household accounting in society on the basis of marriage law. This research is qualitative research which was initiated by determining the scientific framework regarding household habits related to accounting taken from the urf theory in Islamic law, then collecting information from informants consisting of housewives who play a public role to interesting information regarding household accounting that has been carried out so far. This research succeeded in reducing the weakness of household accounting in Indonesia due to the unclear concept of entities within the family household. Based on knowledge of marriage law, it turns out that a musyarakah entity has emerged which applies to inheritance as the main entity in household accounting. This research provides great value by providing insight into the great relevance of accounting practices to households. Moreover, by including marriage law into household accounting, household accounting is truly useful in maintaining the moral values of Sakinah mawaddah wa rohmah and most importantly maintaining the integrity of the household.